Art Education Transformation through Youtube App, and Tik Tok on Children's Self-Development in the Era of Globalization - Frihastyayu Bintyar Mawasti; Hartono Hartono; Tjetjep Rohendi Rohidi; Agus Cahyono (International Conference on Science, Education, and Technology, 2022)
Advances in technology and information are often a double-edged sword. The development of art in the world of entertainment is now very easy to enjoy not only through television, but also through youtube and tik-tok which are applications favored by children. The researcher uses qualitative research with a phenomenological approach to analyze how art education is channeled through video sharing applications that are currently popular with the younger generation, which is related to child development in terms of personality and artistic aspects. The author refers to Piaget's theory of child development which reveals that when a child begins to develop towards the maturity stage, it will experience biological adaptation to its environment which will cause qualitative changes in its cognitive structure. The purpose of writing this article is to analyze the influence of art education related to digital disruption in the era of globalization for children's development, as well as how art is the ideal entertainment world for children. The positive impact of art on social media in the era of globalization makes children more creative, think ahead, and increase self-confidence. While the most severe negative impact is the emergence of addiction or addiction. This article is expected to provide a new picture of art education in accordance with the pattern of child development stages.